The day Jimmy's boa ate the wash - Noble, Trinka Hakes, 1944-; Kellogg, Steven (New York : Dial Press, 1980)
Jimmy's boa constrictor wreaks havoc on the class trip to a farm.
Keywords: Boa constrictor -- Fiction; Snakes as pets -- Fiction; Farms -- Fiction; Schools -- Fiction